A potential utilization of end-of-life tyres as recycled carbon black in EPDM rubber. (April 2018) - Sagar, M.; Nibedita, K.; Manohar, N.; Kumar, K. Raj; Suchismita, S.; Pradnyesh, A.; Reddy, A. Babul; Sadiku, E. Rotimi; Gupta, U.N.; Lachit, P.; Jayaramudu, J.
Highlights: Microscopic characterization of recycled carbon black. Incorporation of recycled carbon black obtained from waste tyre pyrolysis in EPDM rubber. Comparison of recycled carbon black with N550 with respect to cure characteristics, thermal and mechanical properties. Study the effect of heat aging on mechanical properties. Abstract: End-of-life (EOL) tyres and their decomposition present severe environmental concern due to their resistance to moisture, oxygen, natural degradation, etc. Pyrolysis is considered to be the most effective and sustainable process for recycling, due to its eco-friendly process. The current work studied the effect of recycled carbon black (rCB), obtained from the pyrolysis of EOL tyres, on the properties of ethylene propylene diene rubber (EPDM). The rCB was characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and chemical methods. rCB was incorporated solely, into a conventional EPDM formulation and also in combination with N550 carbon black. The physico-mechanical properties of the EPDM vulcanizates, before and after aging, were succinctly studied by SEM, TGA, Differential Scanning Calorimetry (DSC), tensile tests and cross-link density. The average particle size of rCB was observed to be 8 µm and the ash content was observed to be higher when compared to the conventional N550 carbon black, which was evident, by the TGA and SEM-EDX analyses. The reinforcing effect and the cross-link density of the rCB-filled vulcanizates were found to be marginally inferior in comparison to the conventional carbon black (N550). The morphology of the tensile- and tear-fractured surfaces were studied by SEM and it was observed that the breaking mechanism follows the rubber chain detachment from the surface mode.